The Warsaw’s climate research conducted in the Department of Climatology, Faculty of Geography and Regional Studies of the University of Warsaw (1951–2018) - Żmudzka, Elwira (Acta Geographica Lodziensia, 2019)
The article discusses selected aspects of Warsaw’s climate research conducted by employees of the Department of Climatology of the Faculty of Geography and Regional Studies at the University of Warsaw. The climate of cities, mainly Warsaw’s climate, is one of the most important research issues undertaken in this academic center. Of particular importance was establishing, on the initiative of Prof. Wincenty Okołowicz, a meteorological station located on the main campus of the University of Warsaw, in downtown Warsaw. The study presents the main research issues carried out as individual and team works as well as commissioned works and projects. Selected works on the concerned issues are presented. The importance of student diploma theses in research into Warsaw’s climate is also pointed out. Some of the results of the research of the urban heat island, its intensity and conditions are shown. The results confirm the known regularities, but at the same time show the specificity of Warsaw’s climate, resulting from its location, as well as the individual physiographic features and architectural layout of the city. As the urbanization progresses, actions of key importance, especially in the context of the contemporary increase in air temperature, are aimed at reducing exposure to thermal stress and protection against risks related to extreme weather events occurring mainly in the warm half-year.